Efektivitas Sistem Pengadaan Barang/Jasa Pemerintah Secara Elektronik Melalui Aplikasi E-Katalog LKPP pada Kantor Pusat Direktorat Jenderal Perbendaharaan Kementerian Keuangan RI - Rohman Pangkalandari; Muhammad As’Ad (Institut Ilmu Sosial dan Manajemen Stiami, 2025)
This study analyzes the effectiveness of the electronic procurement process of government goods and services through the LKPP e-Catalog system at the Head Office of the Directorate General of Treasury of the Ministry of Finance using the theory of Jones (2017: 379). The results showed that the LKPP e-Catalog has improved procurement efficiency in various aspects, including time, utilization of facilities and infrastructure, resources, and the suitability of goods/services ordered and received. The implementation of this system results in transparency, cost efficiency, and ease of access for various providers, including MSMEs. However, there are several barriers to implementation, such as cybersecurity risks, limited system integration, and organizational resistance to change. To overcome these obstacles, continuous system development, security enhancements, integration with internal platforms, and user training are recommended. Thus, LKPP e-Catalog is expected to further improve the effectiveness and accountability of government procurement of goods and services.